2018
DOI: 10.3389/fninf.2018.00038
|View full text |Cite
|
Sign up to set email alerts
|

FindSim: A Framework for Integrating Neuronal Data and Signaling Models

Abstract: Current experiments touch only small but overlapping parts of very complex subcellular signaling networks in neurons. Even with modern optical reporters and pharmacological manipulations, a given experiment can only monitor and control a very small subset of the diverse, multiscale processes of neuronal signaling. We have developed FindSim (Framework for Integrating Neuronal Data and SIgnaling Models) to anchor models to structured experimental datasets. FindSim is a framework for integrating many individual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…SBML, MATLAB ® SimBiology ® or MOD. Our workflow is modularized into different steps allowing the use of each step depending on the need and ensuring interoperability with other tools, such as those described in a similar endeavor named FindSim (Viswan et al 2018). There are distinct advantages to the workflow, by enforcing a common standard for information exchange, it inherently makes the models more generalizable and reduces the likelihood that simulation results are artifacts of a particular simulator, and nonetheless, it gives users the flexibility to leverage the strengths of each different simulation environment and provides distinct stages of processing that would not be possible in any single simulator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SBML, MATLAB ® SimBiology ® or MOD. Our workflow is modularized into different steps allowing the use of each step depending on the need and ensuring interoperability with other tools, such as those described in a similar endeavor named FindSim (Viswan et al 2018). There are distinct advantages to the workflow, by enforcing a common standard for information exchange, it inherently makes the models more generalizable and reduces the likelihood that simulation results are artifacts of a particular simulator, and nonetheless, it gives users the flexibility to leverage the strengths of each different simulation environment and provides distinct stages of processing that would not be possible in any single simulator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we made two other use cases available for testing other parts of the workflow, with more information in the supplement. More extensive testing was done with a model of the mitogen-activated protein kinase (MAPK) cascade provided by the FindSim workflow (Viswan et al 2018) and results can be found in the supplementary materials.…”
Section: Examples Of Software and Toolboxes Used In Systems Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…The FindSim platform [ 85 ] facilitates collaboration between modellers and experimentalists on a project investigating neuronal signalling in Autism Spectrum Disorders. FindSim makes use of SBML to describe the model, but found it challenging to integrate other standards, especially when it came to capturing experimental data and comparing model outcomes to experiments.…”
Section: Emerging Standardization Needs and Multicellular Modelingmentioning
confidence: 99%